PENGARUH CORPORTE SOCIAL RESPONSIBILITY, UKURAN PERUSAHAAN DAN INTENSITAS PERSAINGAN TERHADAP AGRESIVITAS PAJAK (Studi Empiris pada Perusahaan Manufaktur yang Terdaftar di Bursa Efek Indonesia pada Tahun 2017-2019) - Nadia Rahmadany; Agustinus Santosa Adiwibowo (Diponegoro Journal of Accounting, 2021)
In the era of globalization, the needs of each country are increasingly diverse and increasing. Every country is competing for the welfare of society and making changes for the better in all fields. Taxes are used as the backbone of Indonesia's state income. A company that is one of the taxpayers is not in line with its vision with the government. Companies are trying to reduce spending while the government is trying to make regulations to increase tax revenue. This study aims to examine the effect of corporate social responsibility, firm size, and the intensity of competition on tax aggressiveness. The variables used in the test are corporate social responsibility, firm size, and competition intensity as independent variables, and tax aggressiveness as the dependent variable. This study uses a manufacturing company from 2017 to 2019 with a total sample of 50 samples. Sampling is based on a purposive sampling method that follows certain criteria. Multiple linear regression analysis is a method of analysis used in research. The results showed that corporate social responsibility did not have a significant effect on tax aggressiveness. Meanwhile, company size and competition intensity have a positive effect on tax aggressiveness.